The Influence of Cash Turnover and Inventory Turnover on Return on Assets (ROA) at Adli Banjarmasin Pharmacy - Muhammad Rethan; Fanlia Prima Jaya (PT. Hanken Sukses Jaya, 2025)
The purpose of this study is to determine the effect of cash turnover on return on assets (ROA) at Adli Banjarmasin Pharmacy. To determine the effect of inventory turnover on return on assets (ROA) at Adli Banjarmasin Pharmacy. To determine the relationship between cash turnover and inventory turnover with return on assets (ROA) simultaneously at Adli Banjarmasin Pharmacy. This study uses a quantitative method. The object of this study is Pharmacy’s quarterly financial report starting from 2016-2023. The results of this thesis research indicate that cash turnover partially affects return on assets (ROA), and inventory turnover partially affects return on assets (ROA), while cash turnover and inventory turnover simultaneously affect return on assets (ROA). Discussion of the t-value is greater than the t-table (2.728> 1.70113) and the significant value is greater than the significance level (0.011> 0.05). This means that the Cash Turnover variable partially has a significant effect on Return on Asset (ROA), so H1 is accepted. The t-value is smaller than the t-table value (0.323> 1.70113). and the significance value is greater than the significance level (0.047> 0.05). This means that the Inventory Turnover variable partially has a significant effect on Return on Asset (ROA), so H2 is accepted. The F-table value of 3.33 is obtained from the results of the F-count in this study 3.626 and the significant coefficient (sig) shows an overall value of 0.000. This means that the F-count is greater than the F-table, which is 3.626> 3.33 and the coefficient (sig) 0.045 <0.05. So, it can be concluded that Cash Turnover and Inventory Turnover simultaneously have a significant effect on Return On Assets (ROA), so H3 is accepted.